The Role of B Cells and B Cell Therapies in Immune-Mediated Liver Diseases - Cargill, Tamsin; Culver, Emma L. (Frontiers in Immunology, 2021)
B cells form a branch of the adaptive immune system, essential for the body’s immune defence against pathogens. B cell dysfunction has been implicated in the pathogenesis of immune mediated liver diseases including autoimmune hepatitis, IgG4-related hepatobiliary disease, primary biliary cholangitis and primary sclerosing cholangitis. B cells may initiate and maintain immune related liver diseases in several ways including the production of autoantibodies and the activation of T cells via antigen presentation or cytokine production. Here we comprehensively review current knowledge on B cell mechanisms in immune mediated liver diseases, exploring disease pathogenesis, B cell therapies, and novel treatment targets. We identify key areas where future research should focus to enable the development of targeted B cell therapies.